(untitled) (Biological Sciences - PJSIR, 1997)
Effects of initial size of cotton callus on its further growth in vitro were investigated. It was observed that reduction in initial size/quantity of cultured callus resulted in reduced growth rate. Phytagel was found to be a superior gelling agent compared to agar.Thiamine at its higher concentration promoted the callus growth compared to the lower concentration.